Enhanced Oil Recovery Using Modern Methods of Microbial and Electric Energy - Saeedi, Shahab Alldin; Keshtegar, Masume (Ciência e Natura, 2015)
Various research provided various definition about enhanced oil recovery but generally any method to move oil recovery would be named as enhanced oil recovery.It should be noted that sometimes enhanced oil recovery means third recovery. At the other hand there is agreement about secondary recovery as part of enhanced oil recovery. as most of Iran reservoirs passed second half age and by increase of age, recovery would became very hard, specific methods should be used. Therefore the best scientific and economic method should be selected among various methods.